Common and unique testosterone and 17 beta-estradiol degradation mechanisms in Comamonas testosteroni JLU460ET by transcriptome analysis - Wang, Ze; Chen, Mingming; Liu, Na; Zhao, Yongkang; Ru, Jintao; Qin, Chuanyu; Zhang, Tingdi (Frontiers in Microbiology, 2023)
Strain C. testosteroni JLU460ET was isolated for testosterone and 17 beta-estradiol degradation by our group. In this study, strain C. testosteroni JLU460ET was induced by testosterone and 17 beta-estradiol and then subjected to transcriptome analysis. There were 2,047 upregulated genes after 3 h of testosterone induction, 2,040 upregulated genes after 13 h of testosterone induction, 2,078 upregulated genes after 3 h of 17 beta-estradiol induction, and 2,095 upregulated genes after 13 h of 17 beta-estradiol induction. Significantly upregulated genes were mainly involved in steroid and aromatic compound degradation. A 100 kb steroid-degrading gene cluster was found by transcriptome analysis, which included 92 annotated genes and 58 novel genes. Among them, MucB/RseB and Fiu are secretory proteins for sensing substrates in the environment. MFS-1 and TonB are transporters of testosterone and 17 beta-estradiol. Ring-cleavage enzymes and beta-oxidation enzymes are important for degradation. The genes upregulated by both substrates were almost the same, but the degree of induction by testosterone was higher than that by 17 beta-estradiol. Nine upregulated genes were selected for verification by quantitative real-time polymerase chain reaction (qRT–PCR). The qRT-PCR results were consistent with the transcriptome sequencing results. In this study, the common and unique metabolic mechanisms of testosterone and 17 beta-estradiol were compared by transcriptome analysis in C. testosteroni JLU460ET for the first time.